A Technical Comparison of Human Papillomavirus Genotyping Assays from a Population-Based Cervical Cancer Screening in South Central Ethiopia - Teka B; Gizaw M; Firdawoke E; Addissie A; Sisay TA; Schreckenberger C; Skof AS; Thies S; Mihret A; Kantelhardt EJ; Abebe T; Kaufmann AM (Cancer Management and Research, 2022)
Brhanu Teka,1,2 Muluken Gizaw,2– 4 Ededia Firdawoke,1 Adamu Addissie,3 Tesfamichael Awoke Sisay,3 Carola Schreckenberger,5 Anna Sophie Skof,5 Sarah Thies,5 Adane Mihret,1,6 Eva Johanna Kantelhardt,2,4 Tamrat Abebe,1 Andreas M Kaufmann5 1Department of Microbiology, Immunology and Parasitology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Gynaecology Martin-Luther-University, Halle-Wittenberg, Germany; 3School of Public Health, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 4Institute for Medical Epidemiology, Biometrics and Informatics, Martin-Luther-University, Halle-Wittenberg, Germany; 5Department of Gynecology, Charité – Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin and Humboldt-Universität zu Berlin, Berlin, 13353, Germany; 6Armauer Hansen Research Institute (AHRI), Addis Ababa, EthiopiaCorrespondence: Andreas M Kaufmann, Tel +49 30 450516499, Fax +4930 450-7 564958, Email Andreas.Kaufmann@charite.dePurpose: High-risk Human Papillomavirus (HPV) is the most important cause of cervical cancer. The highest burden of disease is seen in Low- and Low-Middle-Income Countries (LMIC). Several new HPV screening assays have been developed for high-risk HPV (hr-HPV) testing. We compared the performance and adequacy of three HPV genotyping assays on samples from a population of rural women in south-central Ethiopia.Patients and Methods: One hundred and ten cervical swabs from rural women screened for HPV were assayed. HPV DNA was tested using MPG-Luminex Assay, Anyplex II HPV HR Detection, and EUROArray HPV. MPG-Luminex Assay was used as a reference method to compute the sensitivity and specificity of the two commercial assays in detecting hr-HPV infections.Results: Of the 110 samples, MPG-Luminex Assay found 18.2% positive for the 14 hr-HPV and 7.3% for the probable hr-HPV genotypes. Anyplex™ II HPV HR Detection assay and EUROArray HPV Assay identified 21.82% and 12.7% samples, respectively, for the 14 hr-HPVs and both 7.3% for the probable hr-HPV genotypes (κ=0.734). Among the 14 hr-HPV genotypes, the genotype-specific agreement of the three HPV genotyping assays was moderate or better for HPV16, 31, 35, 39, 52, 56, 66 and 68. The aggregated sensitivity in detecting the 14 hr-HPV infections of Anyplex™ II HPV HR Detection and EUROArray HPV assays was high, 100% and 70%, respectively. The specificities of Anyplex™ II HPV HR Detection and EUROArray HPV were 95.6% and 100%, respectively.Conclusion: The three evaluated assays showed similar analytical performance in the detection of hr-HPV infections and moderate or better concordance in HPV genotyping. This study is part of the ongoing cluster-randomized trial that has been registered in clinicaltrials.gov (NCT03281135) on September 13, 2017.Keywords: analytical performance, HPV PCR test accuracy, HPV test complexity, HPV testing, LMIC